Synthesis and characterization of graphene oxide-molecularly imprinted polymer and its adsorption properties for neopterin from aqueous solution - Khoo, Wai Chat (2019)
Neopterin is a useful biomarker for detection of malignant diseases. However, there are only a few study that has been done on the adsorption of neopterin using a graphene oxide-polymer hybrid material such as grapheme oxidemolecularly imprinted polymer (GO-MIP). The aim of this research was to synthesize and characterize GO-MIP, and the details on adsorption study toward neopterin have been thoroughly discussed. GO-MIP with neopterin as the template was synthesized via free radical polymerization method, methacrylic acid (MAA) as the monomer, ethylene glycol dimethacrylate (EGDMA) as the cross-linker, ammonium persulfate (APS) as the initiator, and 8/2 v/v ratio of dimethylsulfoxide/acetonitrile (DMSO/ACN) solution as porogen solvent. The molar ratio of target template, monomer, and cross-linker used was 1:4:16 respectively. Reflux was performed at 50 °C for 24 hours under inert nitrogen atmosphere. Neopterin binding sites were obtained by removing neopterin template from the synthesized GO-MIP via acid washing. A graphene oxide-non imprinted polymer (GO-NIP) without neopterin imprints was prepared with the same methodology. Fourier-transform infrared spectroscopy (FTIR) result for GO-MIP showed a less intense hydroxyl –OH stretching peak and a more intense carboxylic CO- stretching peak compared to GO. Elemental CHNS analysis for GO-MIP showed that the carbon wt% was 4.37% lower and the hydrogen wt% was 3.702% higher compared to GO. A thermal decomposition peak for GO-MIP can be observed at 400 °C with thermogravimetric analysis (TGA) due to the thermal degradation of MAA. Field emission scanning electron microscopy (FESEM) and transmission electron microscopy (TEM) images showed the presence of neopterin binding sites and the structural morphology of GO-MIP hybrid. Neopterin adsorption study was carried out with a mixture of 10 mg GO-MIP and 1 mL neopterin 10 mg/L standard solution. The mixture was stirred at 300 rpm for 60 minutes, then filtered using nylon syringe filter and the supernatant was analyzed using high performance liquid chromatography coupled with fluorescence detector (HPLC-FLD). GO-MIP adsorbed 45.13 % of neopterin while GO-NIP adsorbed just 23.48 %, about twice the amount of neopterin compared to its non-imprinted counterpart. GO-MIP also showed good neopterin selectivity when under the effect of analog compound 6-biopterin, where GO-MIP adsorbed 34.63 % of neopterin but just 18.64 % 6-biopterin. The static adsorption mechanism was studied using Langmuir and Freundlich isotherms, while the adsorption kinetics was studied using Lagergren pseudofirst- order and pseudo-second-order kinetics models. The adsorption mechanism and kinetics were best described using Freundlich isotherm (R2=0.9917) and Lagergren pseudo-second-order (R2=0.9874), respectively. The adsorption capacity at equilibrium was found to be 0.4749 mg/g with the adsorption parameters as described (10 mg GO-MIP, 1 mL neopterin 10 mg/L). The neopterin adsorption method validation was performed via a non-matrixmatched calibration method. The limit of detection (LOD) and the limit of quantitation (LOQ) of the proposed adsorption method were determined to be 0.9126 mg/L and 3.042 mg/L respectively with linearity range (LR) of 1-10 mg/L. The synthesized GO-MIP showed promising adsorption performance towards neopterin and could be developed into a neopterin sensor in the future.